4(2x+3)=13(x-1)

Simple and best practice solution for 4(2x+3)=13(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x+3)=13(x-1) equation:



4(2x+3)=13(x-1)
We move all terms to the left:
4(2x+3)-(13(x-1))=0
We multiply parentheses
8x-(13(x-1))+12=0
We calculate terms in parentheses: -(13(x-1)), so:
13(x-1)
We multiply parentheses
13x-13
Back to the equation:
-(13x-13)
We get rid of parentheses
8x-13x+13+12=0
We add all the numbers together, and all the variables
-5x+25=0
We move all terms containing x to the left, all other terms to the right
-5x=-25
x=-25/-5
x=+5

See similar equations:

| 1.66*6=10*x | | 11+3v-4v=6v-3 | | 6-3x+37=36 | | 3x/10=2x/3-11 | | 27-y=9 | | -1=4(x-4)-(x-6) | | 5-2x+37=36 | | 4-4x+37=36 | | 1.66*6=x*10 | | 1.66/6=x/10 | | 8x-(5x-7)=31 | | -7(3x=-1)=91 | | (x-8)(5x+-6)=0 | | 3h/5-18=304/35 | | 3-4x+37=36 | | (17x+5)+90=180 | | 3(2-x)+3(4x+7)=20 | | 3x/4-7/2=5/6 | | 6x=1=3x=3 | | 19q−12q=7 | | 6(3n+5)=8(5n+2)+7 | | (3x+2)+x=180 | | 4(x-1)+3x=8-4(x-2) | | 4x-7x-8=-13x+x+91 | | 1-3x÷37=36 | | 5(3x+1)/2=55 | | 12x+10=1/8(8x-32) | | 0-5x+37=36 | | 15x+18=6(2x+4)+3x-6 | | C(x)=2x+50-√x^2-36 | | -8(y)=17 | | p=2L+2W;L=44,W=74 |

Equations solver categories